2012
DOI: 10.1111/j.1468-2370.2012.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Routines in Organizations: Existing Literature and New Perspectives

Abstract: Replication of existing routines in new contexts is an important value-creating strategy for organizations. This paper synthesizes the state of research on replication and organizes the literature around two broad themes: forward knowledge flows (i.e. from a replicator to a replicatee) and reverse knowledge flows. The authors show that the theoretical assumptions of existing research leave important questions around the replication of routines unaddressed. More specifically, they identify research gaps in rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 104 publications
1
58
0
7
Order By: Relevance
“…It is research very interesting because demonstrated relation path dependence between performances and routines. Martin Friesl and Joanne Larty highlights two areas for future research: the political dimension of replication strategies and drift in the process of replication (Friesl & Larty, 2013).…”
Section: Theoretical Approaches and Hypothesesmentioning
confidence: 99%
“…It is research very interesting because demonstrated relation path dependence between performances and routines. Martin Friesl and Joanne Larty highlights two areas for future research: the political dimension of replication strategies and drift in the process of replication (Friesl & Larty, 2013).…”
Section: Theoretical Approaches and Hypothesesmentioning
confidence: 99%
“…By applying existing routines to a new organization environment (Szulanski and Winter, 2002, Parmigiani and Howard -Grenville, 2011) [1,2], replication of routines is to be organization value creation (Friesl and Larty, 2013) [3]. Traditional research, evolution economics paradigm, keeps on the analysis of the macro level, and pay less attention to the role and behavior in the new environment of replication, so "black box" of process of replication is not attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…A teoria das rotinas não é uma linha recente de estudos, mas ainda é bastante proficiente, e, dessa forma, os Estudos Baseados na Prática (EBP) podem contribuir com um novo olhar sobre esse fenômeno e no entendimento aprofundado de como e o que realmente as pessoas fazem em suas práticas cotidianas nas organizações (GHERARDI, 2000;PARMIGIANI & HOWARD-GRENVILLE, 2011;HANSEN & VOGEL, 2011;FRIELS & LARTY, 2013). A teoria da prática social (GHERARDI, 2000;ORLIKOWSKI, 2002;FELDMAN & ORLIKOWSKI, 2011;SANDBERG & TSOUKAS, 2011;NICOLINI, 2011;LANNACCI & HATZARAS, 2012;BISPO, 2013aBISPO, , 2013bDIONYSIOU & TSOUKAS, 2013) pode possibilitar novas perspectivas de abordagem que venham a contribuir para o entendimento das rotinas organizacionais como fonte geradora de padrões de ação, que podem recompor e legitimar um repertório de práticas em contexto social.…”
Section: Relevância Do Estudounclassified
“…Deste modo, as rotinas organizacionais são vistas na perspectiva das práticas, sendo que essa abordagem está em fase de ampliação na teoria organizacional (PARMIGIANI & HOWARD-GRENVILLE, 2011;HANSEN & VOGEL, 2011;FRIELS & LARTY, 2013). Entretanto, a sua significativa proeminência decorre de sua peculiaridade em pesquisar as RO em si na ação, e também da relevância desse fenômeno, principalmente em função de sua capacidade de organizing PENTLAND & HAEREM, 2015) e de promulgar o knowing-in-practice (GHERARDI, 2000;ORLIKOWSKI, 2002;AZEVEDO, 2013;BISPO, 2013aBISPO, , 2013b.…”
Section: As Tradições Dos Ebp E Os Seus Desafios Paradigmáticos Aplicunclassified
See 1 more Smart Citation